Delayed Diagnosis of a Diffuse Invasive Gastrointestinal Aspergillosis in an Immunocompetent Patient - S. Guglielmetti; C. M. Jaccard; K. Mühlethaler; A. Bigler; D. Springe; L. Ebnöther; M. Delgado (Case Reports in Critical Care)
Invasive aspergillosis represents a clinical picture frequently associated with host’s immunosuppression which usually involves a high morbidity and mortality. In general, the most frequent fungal entry is the lungs with secondary hematogenous dissemination, but there are other hypotheses like a gastrointestinal portal of entry. There are some rare publications of cases with invasive aspergillosis in immunocompetent patients. We present the case of an immunocompetent patient without any risk factors except for age, ICU stay, and surgical intervention, who developed a septic shock by invasive gastrointestinal aspergillosis as primary infection. Due to the unusualness of the case, despite all the measures taken, the results were obtained postmortem. We want to emphasize the need not to underestimate the possibility for an invasive aspergillosis in an immunocompetent patient. Not only pulmonary but also gastrointestinal aspergillosis should be taken into account in the differential diagnosis to avoid a delay of treatment.